2008
DOI: 10.2217/14622416.9.10.1487
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Susceptibility to Eating Disorders: Associated Polymorphisms and Pharmacogenetic Suggestions

Abstract: Anorexia nervosa (AN), bulimia nervosa (BN) and binge-eating disorder (BED) are characterized by abnormal eating behaviors often resulting in dramatic physical consequences for the patients. The etiology of eating disorders (EDs) is currently unknown; however, a strong genetic contribution is likely to be involved. To date, the majority of genetic studies have focused on candidate genes, and polymorphic variants of genes coding for substances likely to be involved in the etiopathogenesis of EDs have been asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
30
1
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 176 publications
(223 reference statements)
1
30
1
3
Order By: Relevance
“…There is a growing evidence that eating disorders are influenced not only by environmental factors but also by genes of several systems 2,3 : serotonin candidates (serotonin transporter, serotonin receptors 5-HT2A, 5-HT2C, 5-HT1Db, and 5-HT7, tryptophan hydroxylase 1), dopamine candidates (dopamine transporter 1, dopamine receptors DRD2, DRD3, DRD4), noradrenaline candidates (noradrenaline transporter, b3-adrenergic receptor), monoamine-degrading enzyme genes (catechol-O-methyltransferase, monoamine oxidase A), central regulators of feeding and peripheral regulators of feeding genes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…There is a growing evidence that eating disorders are influenced not only by environmental factors but also by genes of several systems 2,3 : serotonin candidates (serotonin transporter, serotonin receptors 5-HT2A, 5-HT2C, 5-HT1Db, and 5-HT7, tryptophan hydroxylase 1), dopamine candidates (dopamine transporter 1, dopamine receptors DRD2, DRD3, DRD4), noradrenaline candidates (noradrenaline transporter, b3-adrenergic receptor), monoamine-degrading enzyme genes (catechol-O-methyltransferase, monoamine oxidase A), central regulators of feeding and peripheral regulators of feeding genes.…”
mentioning
confidence: 99%
“…4,5 The gene coding for the serotonin transporter (5-HTT or SERT) has been suggested as a good candidate for genetic studies on eating disorders. 2 The 5-HTT is an integral membrane protein localized in presynaptic neuronal membranes. It acts taking up serotonin into the presynaptic neurons after its release in the synaptic cleft, with the purpose of terminating serotonin action and recycling it.…”
mentioning
confidence: 99%
“…При обследовании японской популя-ции [30] было установлено, что аллель G полиморфизма MspI (-1438A/G) в промоторном регионе гена 5HT2A ре-цептора увеличивает риск приступообразного переедания в рамках булимии и коморбидных пограничных психиче-ских расстройств. При этом ряд полиморфизмов в генах Журнал неврологии и психиатрии, 8,2016 генетика приступооБразного переедания 5-HT2A рецептора и BDNF обнаружил связь с анорексией [31]. Не выявлено влияния полиморфизма в кодирующей части (cys23ser) гена 5-HT2C рецептора на риск развития булимии и ВЕD у женщин [32].…”
Section: молекулярная генетика веDunclassified
“…СИОЗС оказались достаточно эффективными при лече-нии булимии и BED. Однако соответствующие результа-ты носят предварительный характер [31]. Как правило, фармакотерапия используется в комплексе с психотера-пией и психологическим консультированием, и в целом их комбинации более эффективна, чем только фармако-терапия [55], причем есть точка зрения [56], что эффект психотерапии также контролируется генетически через влияние на черты личности.…”
Section: фармакогенетический подходunclassified
“…Both addictive drugs and palatable foodstuffs exposure produce neuro-adaptations (e.g., a repeated stimulation of mesolimbic DA-ergic neurotransmission) that lead to compulsive drug-and food-seeking behavior [9,11,12]. Moreover, several studies found an implication of genes involved in weight regulation, eating behavior, mood, and stress responsivity [9,13]. Genetic variants in eating disorders have been investigated [14][15][16], and the Taq1A (minor) allele of DA receptors D2 (DRD2) gene is associated with many of substance-misuse disorders [16][17][18].…”
mentioning
confidence: 99%